Reconstruction of Gender Interpretation in Misogynistic Hadiths: Implications for Islamic Education Reform - Yuliharti, Yuliharti; Agustiar, Agustiar; Hasbi, Ridwan; Efendi, Aprijon; Alfiah, Alfiah (Journal of Posthumanism, 2025)
This study focuses on reconstructing gender interpretation in hadiths considered misogynistic and its implications for Islamic education reform. In general, hadith teachings in many Islamic institutions are still dominated by traditional interpretations that often place women in less equal positions. This highlights the need to revisit these interpretations to align them with the principles of gender justice taught in Islam. The research addresses a knowledge gap regarding the lack of studies connecting misogynistic hadith interpretations with the Islamic education system, which has not fully accommodated gender issues. The objective of this study is to provide comprehensive solutions to these issues through more inclusive educational reforms. This research employs a qualitative approach using a case study method, involving in-depth interviews, participant observation, and document analysis at several Islamic educational institutions in Indonesia. Interviews were conducted with scholars, academics, and education practitioners to gain insights into the interpretation of misogynistic hadiths and their impact on teaching materials. The findings reveal significant support from academics and education practitioners for reconstructing hadith interpretations to strengthen gender justice values in Islamic educational materials. This study contributes by offering a fresh perspective that emphasizes the importance of curriculum reform to integrate gender justice principles. The implications of this research are expected to encourage more progressive and responsive education policies regarding gender issues, ultimately fostering a more inclusive and just Islamic education system.